Tres Principios para la Configuración de una Psicología de lo Complejo - Soto, Juan (Cinta de Moebio. Revista de Epistemología de Ciencias Sociales, 2000)
The dialogical principle, the organizational recursivity principle and the hologramatical principle, are the three principles can help us to think the complexity. The first one allows us to think how the duality can stay in the breast of the unit. The second lead us to the understanding of how the products and the effects are, at the same time, causes and products of what produces them. The third, and perhaps the most beautiful of three, refers that the part itself is not only in the everything but rather the everything is also in the part. Three images can help us to clarify these principles: first, the process of mating of the hens produces hens, which produces the process of mating of the hens; second, the hens put eggs of where to come out more hens than put more eggs; third, a hen egg is a hen in potential. The configuration of a psychology of complexity is related with the application of this principles for the analysis of the social reality in several addresses: a) to win complexity in the explanatory and descriptive environments, opening diverse ways of thinking and novel investigation lines, accepting that the theories of the complexity have been related inevitably with the sciences of the behavior; b) to understand that the daily life can be studied from four optics that deserve recognition in the epistemological level of the social psychology: fuzzyness, catastrophic, fractal and chaotic; c) to recognize that reality demands scientific explanations complex and leave the simplicity; d) to renovate the psychology from their base and not from the obedience and the academic subjection.